The Effectiveness of Digital-Based Religious Moderation Learning: A Review of the Literature in the Era of Society 5.0 - Liza Jauharotul Munfarida Al Khurriyyah; Muh. Wasith Achadi; Gondo Adhi Saputra; Fanida Susilowardani; Ahmadan Haquridha Yasyada (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Society 5.0 era, which emphasizes the integration of technology into all aspects of life, demands a transformation in Islamic education, including in the teaching of religious moderation. This study aims to analyze the effectiveness of digital-based religious moderation learning through a literature review approach of relevant articles. Data collection was conducted by selecting articles based on inclusion criteria from databases such as SINTA, Scopus, and Google Scholar, which were then analyzed thematically. The results show that digital-based religious moderation learning holds great potential for internalizing moderation values such as tolerance, justice, and balance, particularly when supported by explicit integration of values into the curriculum, the use of interactive media, value-based teacher training, and project-based learning approaches. However, significant barriers were identified, such as the lack of longitudinal studies, overemphasis on cognitive aspects, technological infrastructure limitations, and the absence of systematic value-based learning design. In conclusion, to ensure the long-term effectiveness of digital-based religious moderation learning, the development of an integrative model that includes critical digital literacy, the strengthening of social values in virtual spaces, and educational policies based on Islamic moderation values is required. This study recommends the need for further longitudinal research and more systematic value-based learning design to support adaptive Islamic education in the Society 5.0 era